2015
DOI: 10.1111/cea.12441
|View full text |Cite
|
Sign up to set email alerts
|

Skin testing for immediate hypersensitivity to corticosteroids: a case series and literature review

Abstract: As the largest case series described, this article provides new evidence for the interpretation of skin tests when investigating possible immediate hypersensitivity to corticosteroids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 22 publications
(43 reference statements)
0
20
0
3
Order By: Relevance
“…Baker et al [18] reported on a case series of 23 patients with suspected corticosteroid hypersensitivity. Almost all of the cases with a positive skin test had a history of anaphylaxis; intra-articular triamcinolone acetonide was the causative agent in 5 out of 8 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Baker et al [18] reported on a case series of 23 patients with suspected corticosteroid hypersensitivity. Almost all of the cases with a positive skin test had a history of anaphylaxis; intra-articular triamcinolone acetonide was the causative agent in 5 out of 8 patients.…”
Section: Discussionmentioning
confidence: 99%
“…In most subjects with IHRs, it is possible to identify the culprit and safe alternative GCs by performing immediate‐reading STs 178‐185 . In the aforementioned review, 74.1% of 112 STs carried out with GCs suspected of being responsible for reactions were positive 181 .…”
Section: Anti‐cytokine/anti‐inflammatory Drugs Used For Mas/cytokine mentioning
confidence: 99%
“…In the allergy workup, negative results in STs should be confirmed with DPTs 180‐185 . DPTs are also recommended to ensure tolerance of alternative preparations 184 .…”
Section: Anti‐cytokine/anti‐inflammatory Drugs Used For Mas/cytokine mentioning
confidence: 99%
“…A hipersensibilidade aos CT, com apresentação imediata ou tardia, tem sido descrita na literatura nos últimos 30 anos 9 . O diagnóstico de uma reação de hipersensibilidade a CT continua a ser um desafio 9 .…”
Section: Artigo De Revisãounclassified